STUDI PENENTUAN JENIS OUTLET LIMBAH CAIR KARET REMAH UNTUK PERTUMBUHAN MIKROALGA DENGAN SISTEM OPEN PONDS [Study of determination the type of crumb rubber waste water outlet for the growth of microalgae with open ponds system] - Tanto Pratondo Utomo; Otik Nawansih; Anggun KOmalasari (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2015)
Waste water of crumb rubber industry is originated from coagulation, milling and leaching stage contains organic material that is derived from serum and rubber particles which haven’t been coagulated yet. The materials are potential to pollute the water therefore the crumb rubber industry must be treated through the wastewater plant. However, the characteristics of waste water are predicted suitable for the cultivation of Nannochloropsis sp. media a biofuel feedstock, especially biodiesel that can be used as an energy source. The purpose of this study was to determine the kind of the outlet of the crumb rubber waste water suitable for growth microalgae with open ponds system. This study was conducted in two phases: the first is the characterization of wastewater. Waste water used is waste water crumb rubber derived from Facultative ponds II (F2), an Aerobic I pond (Ae1), and an Aerobic II pond (Ae2) with a working volume of each 5 L as a three-stage treatment of growth Nannochloropsis sp. media. The second phase is the cultivation of Nannochloropsis sp. as much as 25% v / v of work. The observations those have been done are: microalgae density (OD), analysis of N-NH3, N-total, P-PO4, pH, temperature, content of Chemical Oxygen Demand (COD), Dissolved Oxygen (DO) and dried Yield acquisition. The optimum result of Nannochloropsis sp. growth is on waste water Facultative II pond media with density of cell is about 3.3 x 107 cells / mL. Moreover, it can degrade the organic matter content of waste water crumb rubber in the form of N-NH3 reaches 98%, P-PO4 89%, N-total 92%, and the dry yield of micro algae 0.87g /L.Keywords: waste water, Nannochloropsis sp., microalgae cultivation.